2000
DOI: 10.1002/1099-1611(200011/12)9:6<511::aid-pon469>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial effects of living with an increased risk of breast cancer: an exploratory study using telephone focus groups

Abstract: Research to date has mainly focused on the short‐term psychological impact of genetic risk counselling for breast cancer. This study aimed to explore the long‐term consequences for women of being informed about an increased risk of breast cancer in terms of: the effect on their everyday lives, their coping strategies and their unmet needs in terms of the current service. The participants were 25 women with a family history of breast cancer who had received genetic risk counselling and had consequently been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 23 publications
2
71
0
Order By: Relevance
“…Ten qualitative studies were identified and explored family discord [13], experience, physical, and psycho-social well being of women with breast cancer under the age of 40 who are BRCA1/2 mutation carriers [14], stigma associated with genetic disease [15], moral and social effects of having genetic testing [16], long term coping strategies and unmet needs of women at increased risk for breast cancer [17], experiences of women having prophylactic mastectomy [18,19], responses to BRCA1/2 testing [20][21][22] and how women live with increased risk [23] (See Table 1). Twenty seven quantitative studies were identified (See Table 2).…”
Section: Designmentioning
confidence: 99%
“…Ten qualitative studies were identified and explored family discord [13], experience, physical, and psycho-social well being of women with breast cancer under the age of 40 who are BRCA1/2 mutation carriers [14], stigma associated with genetic disease [15], moral and social effects of having genetic testing [16], long term coping strategies and unmet needs of women at increased risk for breast cancer [17], experiences of women having prophylactic mastectomy [18,19], responses to BRCA1/2 testing [20][21][22] and how women live with increased risk [23] (See Table 1). Twenty seven quantitative studies were identified (See Table 2).…”
Section: Designmentioning
confidence: 99%
“…The draft information pack was piloted on a small group of women living with an increased risk of breast cancer who had participated in a previous study [2]. Twelve of the 25 women who were invited to evaluate the information pack replied to the invitation.…”
Section: Pilot Testing (Stage 10)mentioning
confidence: 99%
“…A telephone focus group study of 25 women who had been attending the South East Scotland familial breast cancer clinic for at least 2 years highlighted unmet needs both for information and psychosocial support [2]. A subsequent larger-scale study of 249 long-term attendees of the clinic identified that a need for up-to-date scientific and psychosocial information was widespread [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations